2014
DOI: 10.1007/s12529-014-9406-6
|View full text |Cite
|
Sign up to set email alerts
|

Social Physique Anxiety and Disturbed Eating Attitudes and Behaviors in Adolescents: Moderating Effects of Sport, Sport-Related Characteristics, and Gender

Abstract: The relationship between SPA and DEAB does not differ according to adolescents' involvement in sport practice or according to their involvement in organized, competitive, or leanness sport practice more specifically. However, higher levels of SPA and DEAB were observed in adolescents involved in individual sports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 66 publications
(157 reference statements)
2
13
0
Order By: Relevance
“…These results are in line with several studies. The study carried out by Lanfranchi, Maïano, Morin & Therme [70], stands out where those young people who practice physical exercise and sport assiduously showed a greater prevalence of suffering from eating disorders when they felt high anxiety. From the field of health, the studies by Oliver, Wardle & Gibson [71] and Wardle, Steptoe, Oliver & Lipsey [72] stand out, where it was observed that those participants who were subjected to stressful situations showed a greater predilection for foods with more sugar and calorie content than those participants who were more relaxed.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in line with several studies. The study carried out by Lanfranchi, Maïano, Morin & Therme [70], stands out where those young people who practice physical exercise and sport assiduously showed a greater prevalence of suffering from eating disorders when they felt high anxiety. From the field of health, the studies by Oliver, Wardle & Gibson [71] and Wardle, Steptoe, Oliver & Lipsey [72] stand out, where it was observed that those participants who were subjected to stressful situations showed a greater predilection for foods with more sugar and calorie content than those participants who were more relaxed.…”
Section: Discussionmentioning
confidence: 99%
“…In support of these theoretical proposals, empirical evidence has been found associating body‐related cognitive processes such as physical appearance comparison (PAC) to DE (Alcaraz‐Ibáñez, 2017; Alcaraz‐Ibáñez, Sicilia, Díez‐Fernández & Paterna, 2020; Fitzsimmons‐Craft, Harney, Brownstone, Higgins & Bardone‐Cone, 2012; Walker, Thornton, De Choudhury, Teevan, Bulik, Levinson & Zerwas, 2015). Similarly, a body‐related affective experience such as social physique anxiety (SPA; i.e., the distressed feelings experienced as a result of believing that the own body could be negatively evaluated by others; Hart, Leary & Rejeski, 1989) has been also consistently associated with DE (Alcaraz‐Ibáñez & Sicilia, 2020; Alcaraz‐Ibáñez et al ., 2020; Fitzsimmons‐Craft, Harney et al, 2012; Lanfranchi, Maïano, Morin & Therme, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Body image concerns, specifically, body dissatisfaction is the precursor of DEAB's. DEABs have been increasingly studied in samples of adolescents that participate in sports [4,8,[23][24][25]. Studies demonstrated that DEABs contribute to poor health and performance in sport, musculoskeletal injury, the development of female and male athlete triad [26][27][28][29], and drop out from sport [30,31].…”
Section: Introductionmentioning
confidence: 99%